2013
DOI: 10.1128/jvi.00708-13
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft- and Src Family Kinase-Dependent Entry of Coxsackievirus B into Human Placental Trophoblasts

Abstract: bMaternal-fetal transmission of group B coxsackieviruses (CVB) during pregnancy has been associated with a number of diverse pathological outcomes, including hydrops fetalis, fetal myocarditis, meningoencephalitis, neurodevelopmental delays, congenital skin lesions, miscarriage, and/or stillbirth. Throughout pregnancy, the placenta forms a critical antimicrobial protective barrier at the maternal-fetal interface. Despite the severity of diseases accompanying fetal CVB infections, little is known regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 92 publications
1
29
0
Order By: Relevance
“…Indeed, follow up studies confirmed that EV71 vRNA was exclusively localized to mucin-2 (MUC2)-positive goblet cells ( Figure 4B, 4C ). As an additional confirmation for the goblet cell specificity of EV71 infection, we also performed immunofluorescence microscopy for VP1 using an immunostaining technique that distinguishes between VP1 localized on the extracellular surface and VP1 localized intracellularly 24 . These studies confirmed the presence of intracellular VP1 only in cells exhibiting goblet cell morphology ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, follow up studies confirmed that EV71 vRNA was exclusively localized to mucin-2 (MUC2)-positive goblet cells ( Figure 4B, 4C ). As an additional confirmation for the goblet cell specificity of EV71 infection, we also performed immunofluorescence microscopy for VP1 using an immunostaining technique that distinguishes between VP1 localized on the extracellular surface and VP1 localized intracellularly 24 . These studies confirmed the presence of intracellular VP1 only in cells exhibiting goblet cell morphology ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 65%
“…Experiments were performed with EV-71 (1095), or E11 (Gregory) that were expanded as described previously 41 . In some cases, experiments were performed with light-sensitive neutral-red viral particles, which was generated as described previously 24 . Briefly, EV71 was propagated in the presence of 10µg/mL of neutral red in the semi-dark and was subsequently purified in semi-dark conditions by ultracentrifugation over a sucrose cushion, as described 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Neutral red-labeled CVB3-RD was prepared as previously described (Delorme-Axford et al, 2013b). For time courses of infection in HT29 cells, CVB was pre-adsorbed to cells for 1 hr at 16°C to synchronize infection.…”
Section: Methodsmentioning
confidence: 99%
“…Although the primary receptor for CVB is CAR, a tight-junction protein, CD55 is recognized as a coreceptor by some coxsackie B virus serotypes (CVB1, CVB3, and CVB5) (646). In polarized intestinal and trophoblastic epithelial cells, CVB binds CD55 on apical membranes and is then transported toward the tight junctions to bind CAR, followed by caveolindependent endocytosis (647,648). Both membrane trafficking and invasion are dependent on lipid rafts and can be disrupted by methyl-␤-cyclodextrin and simvastatin.…”
Section: Enterovirusesmentioning
confidence: 99%
“…Both membrane trafficking and invasion are dependent on lipid rafts and can be disrupted by methyl-␤-cyclodextrin and simvastatin. Like Dr adhesins, virus uptake involves signaling through raft-associated Src kinases (648). In cell cultures, CVB infection can be blocked by soluble CD55 and CD55 antibodies (645,646).…”
Section: Enterovirusesmentioning
confidence: 99%